3a-15+4-2a=-17

Simple and best practice solution for 3a-15+4-2a=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-15+4-2a=-17 equation:


Simplifying
3a + -15 + 4 + -2a = -17

Reorder the terms:
-15 + 4 + 3a + -2a = -17

Combine like terms: -15 + 4 = -11
-11 + 3a + -2a = -17

Combine like terms: 3a + -2a = 1a
-11 + 1a = -17

Solving
-11 + 1a = -17

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1a = -17 + 11

Combine like terms: -11 + 11 = 0
0 + 1a = -17 + 11
1a = -17 + 11

Combine like terms: -17 + 11 = -6
1a = -6

Divide each side by '1'.
a = -6

Simplifying
a = -6

See similar equations:

| x+4+2x+2+3x+10=18 | | 6x-2(x-6)=4(x+1)+2 | | 9*(3+4)= | | 1.5x+3y-z=-8 | | x-x*0.1=86.96 | | -5(1)=8+4m | | x(5+x)=(x*x)+3x+1 | | 12q-4=32 | | 2(3x-4)+5-4x=11 | | 24x+1.8-x+3=16-1 | | 16x=.6x | | 0.8(x-5)=0.4x-20 | | -Rx+5y=-T | | 7x+-5=4x+4 | | 24x+1*8-x+3=16-1 | | f(x)=x(x+1)(x-6) | | -5(0)=8+4m | | (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 | | 3y=9-4x | | 3c+17=8 | | 3x-8x-5=-15 | | 5x-17=3x+4 | | 4q+3=-9 | | p-4+-9=p |

Equations solver categories